Being enjoyably challenged is the key to an enjoyable gaming experience: an experimental approach in a first-person shooter game. (1st January 2018) - Corcos, Anne
ABSTRACT: Applied to video games, Csikszentmihalyi's work on flow evidences that a positive gaming experience is intrinsically self-rewarding and primarily determined by the skill/challenge balance. A multi-layered measure of enjoyment is built to take these components into account. Gamers were asked to report the concentration-enjoyment they experienced during a first-person shooter game, and to better assess the gap between skill and challenge, the challenge enjoyment was also rated. Along with concentration level, concentration enjoyment is used to build a gaming experience typology that accounts for the self-rewarding component. An enjoyment-based challenge mapping is also drawn up, crossing challenge enjoyment and challenge level. The results show that this integrative enjoyment measure strengthens the causal link between challenge and gaming experience. Most importantly, the findings suggest that challenge or concentration-based enjoyment measures outweigh the standard concentration and difficulty measures as they are more likely to ensure a pleasant and positive experience (flow or relaxation) for the gamers. Indeed, regardless of the reported level of challenge, a gamer is more likely to have a positive experience when challenged at a level she perceives as pleasant. This article emphasizes the importance for game publishers of gathering enjoyment-based concentration and challenge assessments to ensure a positive gaming experience and gamers' commitment.